Analisis Peran Orang Tua dalam Membimbing Anak Belajar Daring Di Masa Pandemi Covid-19 pada Tingkat Sekolah Dasar - Sri Lestari; Herniyanti Herniyanti; Reza Ariefka (Institute of Computer Science (IOCS), 2022)
In the aftermath of the spreading of pandemics covid-19 in indonesia , the government with alacrity issued a policy in order to break the chain for the transmission of the virus corona .One of policy are in education sector is learning system might face-to-face with online learning .With a system of learning online becomes many obstacles, so that the role of parents are very is required in teaching the child home studying .Of writing articles aims to understand the role of older people in applying learning at home when the pandemic covid-19. The methodology used a qualitative approach by descriptive method. Data is collected using likert scale consisting of 20 of the survey questions .The population study areas is parents primary schools in east buay in madang .The conclusion of this research is in general the role parents had increased during the students spend at home .Parents consider diterapan effective for online learning.